The role of emotion processing in art therapy (REPAT) intervention protocol - Czamanski-Cohen, Johanna; Weihs, Karen L. (Frontiers in Psychology, 2023)
Psychological and physical health are known to improve with emotion processing, which is becoming aware of bodily sensations, accepting them as information that can be translated into emotion concepts and expressing them symbolically and linguistically as emotions. Art therapy utilizes the visual arts for processing emotions to facilitate self-expression and communication with the goal of improving psychological wellbeing. The mental health of individuals coping with and recovering from cancer is known to benefit from art therapy. The purpose of this paper is to describe the development of the role of emotion processing in art therapy (REPAT) intervention, which is an 8 week, one and a half hour art therapy intervention created to target emotion processing as a primary mechanism of change, through which art therapy has the potential to reduce symptoms (i.e., depression, pain and fatigue) of women coping with breast cancer. To obtain this goal we used template for intervention description and replication (TIDieR) and GUIDance for the rEporting of intervention Development (GUIDED) guidelines for intervention development description, with the goal of ensuring successful implementation for clinical and research use.